Type II collagen peptide is able to accelerate embryonic chondrocyte differentiation: an association with articular cartilage matrix resorption in osteoarthrosis - Elena Vasil'evna Chetina; Elena Vasilyevna Chetina (Научно-практическая ревматология)
Objective: To study the effect of type II collagen peptide (CP) on the decomposition of type II collagen and the differentiation of embryonic chondrocytes of various morphotypes, isolated from the bovine growth plate. Material and methods. Bovine growth plate chondrocytes were separated into morphotypes on a Percoll gradient in accordance with different differentiation stages and then cultured in the presence or absence of 10 ßM of CP. Cartilage explants from patients with osteoarthrosis (OA) were also cultured in the presence of 10 μM of CP. Type II collagen decomposition activity was evaluated by ELISA. Gene expressions were determined by reverse transcription polymerase chain reaction (RT-PCR). Results. The cells having the highest buoyant density on a Percoll gradient (subpopulation A) were represented as early proliferative zone chondrocytes in the growth plate. In their presence of CP, there was increased expression of the genes of transforming growth factor (TGF) β2, parathyroid hormone-related peptide (PTHrP), fibroblast growth factor (FGF) 2, and cyclin B2, which were expressed in the proliferative zone of the growth plate, as well as metalloproteinase matrix (MMP) 13 and collagen decomposition activity. The large cells with the lowest buoyant density on a Percoll gradient (subpopulation B) were represented as hypertrophic chondrocytes. Cultivation of these cells in the presence of CP increased the expression of the genes associated with the terminal chondrocyte differentiation of type X collagen (COL10A1), Indian hedgehog (Ihh), core-binding factor (CBFA) 1 and TGF β1; and the expression of MMP 13 was suppressed. At the same time, collagen decomposition activity in cultured chondrocytes remained unchanged in the presence of CP. Although type II collagen was able to induce the collagen decomposition in the healthy articular cartilage explants, which was attended by the increased expression of the genes associated with the hypertrophic zone of an embryonic growth plate, it did not affect collagen decomposition rate in the cartilage of patients with OA. Conclusion. The effect of CP on gene expression and collagen decomposition activity depends on the morphotype of embryonic chondrocytes. Lack of effect of CP on collagen decomposition activity in both the embryonic hypertrophic chondrocytes and the cartilage explants from OA patients supports the hypothesis that the hypertrophic morphotype is a dominant morphotype of articular chondrocytes in OA. Moreover, collagen decomposition products can be involved in the resorption of matrix in OA and in the maintenance of chronic nature of the pathology.